Keanekaragaman Serangga Predator Pada Perkebunan Kelapa Sawit Di Lahan Bukaan Baru Dan Bukaan Lama - Danial, Ahmad; Siska Efendi (Jurnal Riset Perkebunan, 2020)
The diversity of predatory insects was studied in recent and old lands in Dharmasraya from April to July 2017. The objective was to study the diversity of predatory insects between recent and old plantations of oil palm. The sampling locations were Pulau Punjung, Timpeh and Koto Besar Districts. The method used in the study was Purposive Random Sampling. Insects were collected using the insect net and chemical knockdown. Identification was carried out at the Laboratory of Insect Bioecology, Faculty of Agriculture, Andalas University. Diversity and evenness of predatory insects in several oil palm plantations in Dharmasraya Regency was classified as medium, namely (H '<1), and (E <0.76). There were 11 families and 6 orders found. The abundant family was formicidae.